2016
DOI: 10.1111/jdi.12575
|View full text |Cite
|
Sign up to set email alerts
|

Sudoscan is an effective screening method for asymptomatic diabetic neuropathy in Chinese type 2 diabetes mellitus patients

Abstract: Aims/IntroductionThe aim of the present study was to use the sudomotor function test, Sudoscan, as a screening method for the evaluation of asymptomatic diabetic distal symmetric polyneuropathy in Chinese type 2 diabetes patients. As a result, more attention could be paid to those asymptomatic patients who could be easily neglected and underdiagnosed in everyday clinic.Materials and MethodsA total of 394 Chinese type 2 diabetes patients were enrolled and tested for symptoms and clinical signs of neuropathy usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 26 publications
(40 reference statements)
3
34
1
5
Order By: Relevance
“…With regard to sudomotor assessment, we found that hands and feet ESC were lower in participants with CAN and DPN and were significantly related to all cardiovascular tests (in particular with deep breathing test: P < .0001) and the autonomic score, to the scores of neuropathic symptoms and signs, and to VPT, but not to thermal thresholds. These findings confirm previous observations of correlations of hands and feet ESC with clinical neuropathy scores (ie, NIS‐LL, UENS and MNSI, NDS and NSS, TCNS), deep breathing, Valsalva test, CARTs‐based autonomic score, VPT, and thermal thresholds, with the lowest significance for the latter . In the current study, feet ESC showed a fair diagnostic accuracy for CAN, in particular for confirmed CAN with an AUC of 0.92, while the abnormality of hands or feet ESC had the best sensitivity for confirmed CAN (83%) and the best specificity for DPN (67%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With regard to sudomotor assessment, we found that hands and feet ESC were lower in participants with CAN and DPN and were significantly related to all cardiovascular tests (in particular with deep breathing test: P < .0001) and the autonomic score, to the scores of neuropathic symptoms and signs, and to VPT, but not to thermal thresholds. These findings confirm previous observations of correlations of hands and feet ESC with clinical neuropathy scores (ie, NIS‐LL, UENS and MNSI, NDS and NSS, TCNS), deep breathing, Valsalva test, CARTs‐based autonomic score, VPT, and thermal thresholds, with the lowest significance for the latter . In the current study, feet ESC showed a fair diagnostic accuracy for CAN, in particular for confirmed CAN with an AUC of 0.92, while the abnormality of hands or feet ESC had the best sensitivity for confirmed CAN (83%) and the best specificity for DPN (67%).…”
Section: Discussionsupporting
confidence: 91%
“…The only relationship between ESC and clinical variables was that of mean ESC feet with triglycerides (rho = −0.273, P = .0065). In the analysis of covariance after adjustment for triglycerides, the significant differences in mean ESC feet between the groups with and without CAN and with and without 13,14 Valsalva test, 13 CARTs-based autonomic score, 14 VPT, 14,20,21,41 and thermal thresholds, with the lowest significance for the latter. 13 In the current study, feet ESC showed a fair diagnostic accuracy for CAN, in particular for confirmed CAN with an AUC of 0.92, while the abnormality of hands or feet ESC had the best sensitivity for confirmed CAN (83%) and the best specificity for DPN (67%).…”
Section: Resultsmentioning
confidence: 93%
“…Significant progress has been made to develop point-of-care devices (POCD) that are capable of diagnosing early, subclinical neuropathy. Papanas [39,40] and Sudoscan [41,42].…”
Section: Recent Developments In State-of-the Art Point-of-care Devicementioning
confidence: 99%
“…Sudomotor function has been proposed as a surrogate marker for the small fibre involvement in DPN [41,42,59]. Sudoscan, provides a quantitative measurement of sudomotor function within 3-minutes.…”
Section: Sudoscanmentioning
confidence: 99%
“…11 Autonomic dysfunction could even be the common clustering of FM, chronic fatigue syndrome, irritable bowel syndrome, and interstitial cystitis, and underlie their pathogenesis. 12 Adelta and C nerve fibers, involved in painful and thermal perception, also innervate sweat glands that are linked to the autonomic nervous system, [13][14][15][16] and sweat gland innervation could be dysfunctional because of an alteration of these nerve fibers. Such a dysautonomia may be a detectable abnormality in diabetic SFN, 17 familial amyloid polyneuropathy, or Fabry's disease, 15,[18][19][20][21][22] and has been studied using an electrophysiological noninvasive tool (Sudoscan; Impeto Medical, Paris, France) that measures electrochemical skin conductance (ESC).…”
Section: Introductionmentioning
confidence: 99%